2008
DOI: 10.1016/j.crci.2007.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Blue-phase drops on a glass interface and their decoration at the cholesteric transition

Abstract: Free-surface drops of blue phase attached to a glass slide present topologically concentric lines, which we first believed to be steps at the air interface, as this was often observed in smectic drops or in other liquid crystals. Actually these contours lie at the glass interface, or in its close vicinity, but do not really form steps. While the existence of steps at the air interface cannot be excluded, we did not observe them in this study. Reproducible decorations were observed at the transition from the bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…In a strong electric eld, the well-ordered BP III phase was found near substrates, resulting in a sharper reection peak, corresponding to the higher periodicity of DTCs. Furthermore, Bouligand et al directly observed a topological pattern in a droplet of BPs on glass, 27 which exhibited herring-bone-type N* textures during the phase transition from BP to N*. These previous studies provide insight into the inuence of the air boundary on the BP droplet in our system.…”
Section: Resultssupporting
confidence: 58%
“…In a strong electric eld, the well-ordered BP III phase was found near substrates, resulting in a sharper reection peak, corresponding to the higher periodicity of DTCs. Furthermore, Bouligand et al directly observed a topological pattern in a droplet of BPs on glass, 27 which exhibited herring-bone-type N* textures during the phase transition from BP to N*. These previous studies provide insight into the inuence of the air boundary on the BP droplet in our system.…”
Section: Resultssupporting
confidence: 58%
“…[5,10] Within a narrow temperature range three thermodynamically stable blue phases (BP-III, BP-II and BP-I) exist, which can be usually observed on cooling from Iso to Ch, but sometimes on heating from Ch to Iso [3,9,11] and vice versa with thermal hysteresis. [11][12][13] The so-called 'fog' blue phase (BP-III) is amorphous with a local cubic lattice structure in the director field, which appears over a very narrow temperature range between BP-II and the Iso, [3,[14][15][16][17] while BP-II and BP-I have a fluid three-dimensional periodic structure in the director field with simple cubic and body-centred cubic symmetry, respectively. [6][7][8]15,16,18] For BP-I the elementary cell (lattice) size changes with temperature; while for BP-II there is not temperature change in the lattice size.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] The so-called 'fog' blue phase (BP-III) is amorphous with a local cubic lattice structure in the director field, which appears over a very narrow temperature range between BP-II and the Iso, [3,[14][15][16][17] while BP-II and BP-I have a fluid three-dimensional periodic structure in the director field with simple cubic and body-centred cubic symmetry, respectively. [6][7][8]15,16,18] For BP-I the elementary cell (lattice) size changes with temperature; while for BP-II there is not temperature change in the lattice size. [19] According to the theory, [19] structures of BPs can be described as 'double twist' cylinders (in which the director twists simultaneously in two independent directions), filling up large volumes and disclinations.…”
Section: Introductionmentioning
confidence: 99%
“…But liquid crystals are much more than materials employed in image display; they also pave the way to switchable adaptive and nonlinear optics, addressable waveguides and sensor materials [10]. At the same time, liquid crystals are ideal materials to study a wide range of fundamental phenomena in soft matter physics and material science [11,12], such as phase transitions, chirality [13], ferroelectricity in fluids [14,15], pattern formation [16], colloidal and polymer composites [17][18][19][20][21] or defect structures and dynamics [22,23], and living matter [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…10 At the same time, liquid crystals are ideal materials to study a wide range of fundamental phenomena in so matter physics and material science, 11,12 such as phase transitions, chirality, 13 ferroelectricity in uids, 14,15 pattern formation, 16 colloidal and polymer composites [17][18][19][20][21] or defect structures and dynamics, 22,23 and living matter. [24][25][26][27] 1.1 The self-organized order of liquid crystals Liquid crystals are partially ordered uids which are thermodynamically stable between the (isotropic) liquid and the (threedimensionally ordered) crystal (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%